Taxing women's bodies: the state of menstrual product taxes in the Americas - Alhelí Calderón-Villarreal (Elsevier, 2024)
Summary: The taxation of menstrual products has been identified as unfair, imposing economic burden on people who menstruate based simply on a biological difference. These taxes have been described as major contributors to menstrual poverty. Although they have been debated among governments, and a focus of political activism, academic literature has largely neglected the issue. Here I comprehensively reviewed the status of menstrual product taxes for all countries and populated territories in the Americas in 2022. Data from 57 countries and territories, and 78 states (those of the United States and Brazil) were included. Since 2012, 10 countries and territories have eliminated taxation on menstrual products-Jamaica, Canada, Saint Kitts & Nevis, Trinidad & Tobago, Guyana, Colombia, Puerto Rico, Mexico, Ecuador, and Barbados. Nevertheless, menstrual product taxes were still applied in 63.2% of locations in 2022, with an average tax rate of 11.2% (ranging from 1.0% in Costa Rica to 22.0% in Uruguay). The average woman of reproductive age in the Americas experienced a menstrual product tax rate of 5.8% in 2022. In sum, despite activism and progress, most of the region continues to employ discriminatory taxation against people who menstruate, with particularly high taxation rates concentrated in South America.